WOMEN'S EMPOWERMENT, CADRE TRAINING, AND MASS EXAMINATION FOR CERVICAL CANCER DETECTION - Ratna Dwi Jayanti; Ivon Diah Wittiarika; Rize Budi Amalia (Jurnal Layanan Masyarakat (Journal of Public Services), 2023)
Cervical cancer is the most common type of cancer in women and the main reason people die from cancer in poor countries like Indonesia. Cervical cancer is a type of cancer that is caused by the Human Papillomavirus (HPV) and can be dangerous to a woman's health. Cervical cancer has the second most cases and deaths in the world, after breast cancer. The East Java Provincial Health Office's Health Profile for 2021 says that Trenggalek is an area with a low rate of cervical cancer screening. So, we started doing community service projects to make more people aware of cervical cancer. This community event began with drinks for the staff and a talk about cervical cancer and how to find it early. Some of the things that are done are health education about cervical cancer and ways to find it early. During this practice, women of reproductive age (WUS) were also asked to take part in a free Visual Acetate Acid (VIA) test done by the team. The next event was a free VIA test, which 21 WUS students took part in. The results of the VIA test showed that 20 people had bad VIA and one person had good VIA. The team then sent people who had a good VIA to get more care. Women, cadres, and other important people in the community can learn more about cervical cancer through community service. However, community service in other areas is needed in the coming year so that this issue can be brought up and the community can benefit from it, especially since cervical cancer is on the rise. People also think that this would change how women with cervical cancer get their treatments and improve their quality of life. Â